Perceptions of patient safety culture among healthcare employees in tertiary hospitals of Heilongjiang province in northern China: a cross-sectional study. (19th April 2018) - Li, Ying; Zhao, Yanming; Hao, Yanhua; Jiao, Mingli; Ma, Hongkun; Teng, Baijun; Yang, Kai; Sun, Tongbo; Wu, Qunhong; Qiao, Hong
Abstract: Objective: Assessing the patient safety culture is necessary for improving patient safety. Research on patient safety culture has attracted considerable attention. Currently, there is little research on patient safety culture in China generally, and in Heilongjiang in northern China specifically. The aim of the study is to explore the perception of healthcare employees about patient safety culture and to determine whether perception differs per sex, age, profession, years of experience, education level and marital status. Design: Cross-sectional study. Setting: Thirteen tertiary hospitals in Heilongjiang, northern China. Participants: About 1024 healthcare employees. Main Outcome Measure: The perception of healthcare employees was measured using the safety attitude questionnaire, which include six dimensions. Higher scores represented more positive attitudes. An analysis of variance was used to compare socio-demographic differences per position, marital status and education; t -tests were used for sex, age and experience. Results: A total of 1024 (85.33%) valid questionnaires were returned. The mean score of the six dimensions was 73.74/100; work conditions (80.19) had the highest score of all the dimensions, and safety climate (70.48) had the lowest. Across distinct dimensions, there were significant differences in perceptions of patient safety culture per sex, age, years of experience, position, marital status and education level ( P < 0.05). Conclusions: The findings can help in assessing perceived patient safety culture among healthcare employees and identifying dimensions that require improvement. Interventions aimed at specific socio-demographic groups are necessary to improve patient safety culture.